Permeability to value in healthcare innovation procurements: a framework for design and assessment - Rossana Alessandrello; Victòria Valls-Comamala; Ion Arrizabalaga; Uxío Meis-Pinheiro; Olman Elizondo-Cordero; Ramon Maspons; Anna Garcia-Altés (Academia Medicine and Health, 2026)
Introduction: To address emerging health system needs that existing solutions fail to meet, public administrations must foster the development, implementation, adoption, and scaling of new goods and services. Innovation procurement allows the public sector to act as a promoter of research and development aimed at creating appropriate solutions to identified needs through pre-commercial procurement (PCP) or as an early adopter of innovative solutions and services that are not yet widely available commercially while requiring evidence of the value they provide to the impacted stakeholders through public procurement of innovation (PPI). Materials and methods: This article proposes a methodological framework for designing and implementing needs-driven public contracts that are “permeable to value,” meaning that value is generated and recognized throughout the contract lifecycle. The framework was applied to three European Commission co-funded innovation procurement initiatives: two cross-border PCPs and one PPI. Results: Application of the framework demonstrated its feasibility in supporting public buyers to consider the perspectives of multiple stakeholder groups and systematically assessing the value as it is generated through innovation procurement. Across the three cases, the framework provided a structured approach to integrating stakeholder needs and value-related considerations into procurement design and implementation. Conclusions: The proposed framework may support more value-oriented innovation procurement practices by helping public buyers incorporate stakeholder perspectives and monitor value generation over time. As such, it offers a practical approach that may contribute to strengthening the outcomes of public investments in innovation.